Incidence of socioeconomic school segregation on academic performance A study from Peru - Murillo, F. Javier; Carrillo, Sandra (Education Policy Analysis Archives, 2021)
The objective of this research is to estimate the incidence of socioeconomic school segregation in the academic performance of students. For this purpose, data mining was carried out using the data of the Census Evaluation of Students (ECE) of the Ministry of Education of Peru, through Multilevel Models with three levels of analysis (region, school and student). The Hutchens' Square Root Index was used to estimate the magnitude of segregation in each school. The sample consisted of 502,521 2nd grade secondary students from 12,862 schools in the country. The results show that school segregation has a direct and measurable impact on performance in the three areas analyzed, and even helps to explain more than the average socioeconomic level of the school. Likewise, the concentration of students from families with lower socioeconomic levels in the school makes performance lower in the three areas; while the concentration of students from families with higher socioeconomic levels makes performance better, also in the three areas. This study provides solid evidence of how school socioeconomic segregation affects the efficiency of the educational system, as well as the equality of educational opportunities for all.